International Standards for Regulation of Competition Liability - Yu. Monastyrsky (Московский журнал международного права)
Let me thank the authors of this conference for the granted opportunity to speak on a most important topic regarding responsibility for non-compliance with competition law. In the narrow legal sense, such responsibility means any penalties being imposed on a violator. They are the main tool for regulation, because their effectiveness, clearness, efficiency and predictability should force any person to comply with the regulatory and, as concerns competition, any personal prescriptions issued by the competent authorities. If an enforcement mechanism is imperfect, then it will promote disorder rather than order. According to the law, a guilty person may incur administrative, civil or criminal liability. The third antimonopoly package contains a number of novelties in this regard.